Executive leadership and teacher performance in the district of Amarilis - Huánuco – 2013 - Barrios-Valer, Edwin (2019)
The present research had as general objective: To determine the relationship between the executive leadership and teacher performance in the educational institutions of the district Amarilis – Huánuco 2013. Concerning the type of study used was descriptive correlational, as in the first described in detail the variables under study, and later establish the degree of relationship between the variables: management leadership and teacher performance, in terms of design research chose the Descriptive - correlational, taking into account the characteristics of the work, the technique used was a survey, two instruments: questionnaires. The population covered by the present investigation were: the management and staff of ten schools Amarilis district, in the province of Huánuco, all of which are 18 managers and 260 teachers, with reference to the sample, it is she made through non-probability sampling discretion of the investigator, the same that had 6 managers and 85 teachers. In the discussion of this research it was validated with the results of the testing of the hypothesis, where the test "r" of Pearson, confirms that there is a significant relationship between the executive leadership and teacher performance of educational institutions level secondary Amarilis district, in the province of Huánuco, in 2013, as the value of r = 0.940, means that there is a high positive relationship and validating the research hypothesis.